CALIDAD DE VIDA RELACIONADA CON LA SALUD EN TUBERCULOSIS: REVISIÓN SISTEMÁTICA Y METANÁLISIS - Natalia Giraldo (Asociación Colombiana de Infectología, 2018)
Objective: To perform a metanalysis on the effect of the tuberculosis on the dimensions of the SF-36. Methods: Systematic review and meta-analysis, following the PRISMA guide. The reproducibility was guaranteed and methodological quality was evaluated with STROBE guide. Random effects meta-analysis was performed using the Dersimonian and Laird's tests, Begg, Egger and sensitivity analyzes in EPIDAT 3.1. Results: We included 35 studies with 12 159 people and eight different constructs of quality of life. In the SF-36, people with tuberculosis had a lower score than healthy controls, with differences of 51.5 points in physical function and mental health, 47.1 in social performance, 41.1 in general health, 33.7 in energy, 27.4 in emotional performance, 24.9 in physical performance and 5.7 in body pain. Conclusion: There is a high availability of quality of life constructs for people with tuberculosis, the disease generates negative impacts on physical function, mental health and social performance, which evidences the need for a multidimensional and interdisciplinary approach for this population.